REVIEW OF MCCORMACK CLASSIFICATION FOR THORACOLUMBAR SEGMENT FRACTURES - SEBBEN,ANDRÉ LUÍS (2017)
ABSTRACT Objective: The aim of this study was to evaluate the success and complications rates of thoracolumbar fractures with a score equal or superior to 7 according to the load sharing classification (McCormack), surgically treated with short posterior fixation at three points. Methods: We evaluated 40 patients with thoracolumbar fractures and score by the load sharing classification greater than or equal to 7, treated exclusively by surgery by short posterior fixation. We assessed epidemiological data, increased kyphosis, loss of vertebral body height and complications at 2-year follow-up. Results: Although there was a statistically significant increase in kyphosis and a decrease in vertebral height, there was no clinical repercussion. Conclusion: We conclude that the McCormack classification is not a fundamental predictor for indication of anterior approach complementary to the short posterior fixation.